Літолого-стратиграфічні умови закарстування гіпсової товщі баденію Покуття (с. Одаїв, печера Думка) - Костюк, Уляна; Рідуш, Богдан (My University, 2023)
The Carpathian Foredeep is one of the largest evaporite basins and contains unchanged gypsum sediments. Gypsum sediments contain differentiated and primary selenite facies. The process of the sediment accumulation was intermitted; there are variability in the sulfate thickness: horizontally and vertically. Speleomorphogenetic method can help to understand lithological features on karst development.
Lithology-stratigraphic features of karstification of badenian gypsum layer in Pokuttya (Odaiv Village, Dumka Cave)
Keywords: гіпс; карст; літологія; стратиграфія; gypsum; karst; lithology; stratigraphy